(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The clinical manifestations of autoimmune rheumatoid arthritis (RA) are not only due to joint involvement, but also due to systemic (extra-articular) manifestations. The most frequent of them are orofacial signs and symptoms, such as hyposalivation, xerostomia, temporomandibular disorders, catarrhal, aphthous, ulcerative lesions of the oral mucosa, periodontal diseases, dysphagia and dysphonia. However, the peculiarities of the development of pathology of hard tissues of teeth and periodontal diseases remain incompletely understood. The results of clinical and clinical-laboratory examinations revealed that patients in RA-P were in a significantly more unfavorable situation than those examined in the subgroup of RA-1 and control groups. The examined patients in both subgroups of the main group of RA-1 and RA-P had unsatisfactory oral hygiene. OHI-S index values increased with increasing duration of the disease and degree of severity of inflammatory phenomena of general systemic pathology. The RA-P subjects had on average 1.24 times higher intensity of dental caries compared to the RA-1 subjects, and 1.96 times higher indices of the control group. Gingival bleeding was 1.35 times more pronounced compared to RA-1 examinees. IR in RA-P is 2.14 times more pronounced in comparison with those examined in the control group. All these changes are observed against the background of reduced salivary secretion of the examined subgroup of RA-P in 1,4 times in relation to RA-1 and in 1,73 times in relation to the values of the control group, increased in 1,2- and 1,4-times viscosity of RG in relation to RA-1 and control groups. Decreased pH values by 1.01 and 1.21 relative to RA-1 and control groups.